1988
DOI: 10.1002/fld.1650080602
|View full text |Cite
|
Sign up to set email alerts
|

Curvature‐compensated convective transport: SMART, A new boundedness‐ preserving transport algorithm

Abstract: SUMMARYThe paper describes a new approach to approximating the convection term found in typical steady-state transport equations. A polynomial-based discretization scheme is constructed around a technique called 'curvature compensation'; the resultant curvature-compensated convective transport approximation is essentially third-order accurate in regions of the solution domain where the concept of order is meaningful. In addition, in linear scalar transport problems it preserves the boundedness of solutions. Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
441
1
18

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 708 publications
(464 citation statements)
references
References 8 publications
4
441
1
18
Order By: Relevance
“…The CUBISTA scheme (Convergent and Universally Bounded Interpolation Scheme for the Treatment of Advection) has the advantage over more classical schemes, like the SMART scheme of Gaskell and Lau [10], of promoting iterative convergence when used with implicit methods. It has been found that this high-resolution scheme is accurate and very stable, thus being very adequate for the simulation of viscoelastic flows [4,8].…”
Section: Governing Equations and Numerical Methodsmentioning
confidence: 99%
“…The CUBISTA scheme (Convergent and Universally Bounded Interpolation Scheme for the Treatment of Advection) has the advantage over more classical schemes, like the SMART scheme of Gaskell and Lau [10], of promoting iterative convergence when used with implicit methods. It has been found that this high-resolution scheme is accurate and very stable, thus being very adequate for the simulation of viscoelastic flows [4,8].…”
Section: Governing Equations and Numerical Methodsmentioning
confidence: 99%
“…In the current model, commercial CFD code PHOENICS was used to solve a two-phase, three-dimensional flow. A staggered grid was employed with the differencing scheme SMART 50) to solve the partial differential equations by converting it to algebraic finite volume equations. The equations are solved iteratively using the IPSA algorithms.…”
Section: Geometry and Mesh Structurementioning
confidence: 99%
“…To improve stability and resolution, we discretize the convective terms for the level set function and its reinitialization equation by employing the SMART [7] and ENO schemes [20]. The SMART scheme is in fact a second-order TVD scheme [15], although it is not included in the TVD region of Sweby [23].…”
Section: Tvd and Eno Schemes For The Convective Term Of The Interfacimentioning
confidence: 99%